REVALUASI ASET TETAP PADA BADAN USAHA MILIK NEGARA UNTUK MENEKAN PAJAK PENGHASILAN - Hastuti Hastuti; Endah Dwi Kusumastuti (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2017)
Abstract: The revaluation of property, plant and equipment is the re-appraisal of the company's fixed assets. Revaluation is allowed by the company with permitted methods and often done to increase the value of the company's assets. This research conducted a reassessment of fixed assets of a state-owned enterprises namely PT. Pegadaian Persero by using net present value. The value of property and equipment after revaluation amounted to Rp 3,870,481,782,801. The income tax (efficiency) generated if the company re-values its fixed assets for tax purposes is Rp 410,835,968,331 or 59.81% in percentage. Tax planning using revaluation of fixed assets has a high level of efficiency and can save the company's tax burden. So it can be concluded that the method of tax planning by using fixed asset revaluation is not included into tax smuggling (tax evasion). Revaluation of fixed assets for the purpose of this taxation, also supported by Regulation of the Minister of Finance No. 79 / PMK.03 / 2008 concerning Revaluation of Fixed Assets of Companies for Taxation Purposes.Keywords: Revaluation of Property, Plant and Equipment, Net Present Value, Income Tax